The unconstitutional of the army disciplinary regulation due to the rule of law (Euro-Latin American Journal of Administrative Law, 2020)
The constitutional adoption of the Rule of Law as one of the fundamentals of the Brazilian state implies the recognition of its principles as the structuring of the entire national legal system. Beyond, from all these principles derive guarantees that, for being set out in the fifth article of the Federal Constitution, receive the formal status of a fundamental right, being applied to them the principle of maximum effectiveness. As some of these principles are intended to guarantee the citizen's rights against the State's sanctioning activity, because of the principle of maximum effectiveness application, it is recognized that there is a Common Sanctioning Core, from which derive all state punitive activity principles, being among them the principle of legality. Since there are no ontological differences between administrative and criminal infractions, but only formal, the component principles of Common Sanctioning Core are equally applied to Criminal Law and Sanctioning Administrative Law. Thus, all the corollaries of the principle of legality also rule Disciplinary Law. Thus, it is concluded that the Army Disciplinary Regulation is unconstitutional, due to the non-observance of the principles of taxation and legal reserve, which affects the fundamental right of ample defence, legality and, consequently, the Rule of Law as a whole.